Gender Gap in Education in West Kalimantan: Analysis of the Regency/City Human Development Index in the 2021-2023 Period - M Zainul Hafizi (International Journal of Applied Educational Research (IJAER), 2024)
This study evaluates the gender gap in education in West Kalimantan through an analysis of the Human Development Index (HDI) for the 2021-2023 period. The goal is to identify the differences between men and women in the education sector in different districts/cities, as well as explore the factors that cause these inequalities. With a descriptive approach and secondary data analysis from the Central Statistics Agency, it was found that most districts/cities still experience significant gender inequality. For example, Bengkayang Regency recorded the largest gap with a difference in HDI between men and women of 12.03 points, while Sambas Regency showed a smaller gap with an increasing trend for women. This study emphasizes the importance of more inclusive policies to improve access and quality of education for women, especially in disadvantaged areas. In addition, raising awareness of the importance of gender equality in education is considered important to create sustainable change. The results of this study contribute to the development of a more equitable education policy in West Kalimantan.